2012
DOI: 10.1002/chir.22108
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Enantioselectivity in the SULT1A3‐catalyzed Sulfoconjugation of Normetanephrine Enantiomers: An In Vitro and Computational Study

Abstract: (1R)-Normetanephrine is the natural stereoisomeric substrate for sulfotransferase 1A3 (SULT1A3)-catalyzed sulfonation. Nothing appears known on the enantioselectivity of the reaction despite its potential significance in the metabolism of adrenergic amines and in clinical biochemistry. We confronted the kinetic parameters of the sulfoconjugation of synthetic (1R)-normetanephrine and (1S)-normetanephrine by recombinant human SULT1A3 to a docking model of each normetanephrine enantiomer with SULT1A3 and the 3'-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The other important function of SULT1A3/4 in vivo was the modulation of neurotransmitter homeostasis by metabolizing catecholamines, such as DA and isoprenaline. 23 DA is highly distributed in the brain, 24 gastrointestinal tract, 10 and liver cells. 25 By performing ultra-high-pressure liquid chromatography-tandem mass spectrometry (UHPLC/MS/ MS), we found that endogenous DA levels in HCC tissues were extremely lower than those in adjacent tissues (Figure 2(c)).…”
Section: Discussionmentioning
confidence: 99%
“…The other important function of SULT1A3/4 in vivo was the modulation of neurotransmitter homeostasis by metabolizing catecholamines, such as DA and isoprenaline. 23 DA is highly distributed in the brain, 24 gastrointestinal tract, 10 and liver cells. 25 By performing ultra-high-pressure liquid chromatography-tandem mass spectrometry (UHPLC/MS/ MS), we found that endogenous DA levels in HCC tissues were extremely lower than those in adjacent tissues (Figure 2(c)).…”
Section: Discussionmentioning
confidence: 99%
“…With this compound we obtained an α op of above 3 with SPA 2 , which is sufficient for efficient large scale resolution of this biologically relevant molecule. 58 Overall this shows how important the 1,2-amino-alcohol motif is and how specific its interactions with the phosphoric acid via H-bonding are. Altering the chain length between moieties, increasing the steric bulk around these positions or removing H-bond donor or acceptor positions results in a total loss of selectivity.…”
Section: Resultsmentioning
confidence: 95%